2020
DOI: 10.1186/s41235-020-00228-3
|View full text |Cite
|
Sign up to set email alerts
|

Emotional judgments of scenes are influenced by unintentional averaging

Abstract: Background: The visual system uses ensemble perception to summarize visual input across a variety of domains. This heuristic operates at multiple levels of vision, compressing information as basic as oriented lines or as complex as emotional faces. Given its pervasiveness, the ensemble unsurprisingly can influence how an individual item is perceived, and vice versa. Methods: In the current experiments, we tested whether the perceived emotional valence of a single scene could be influenced by surrounding, simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
1
8
2
Order By: Relevance
“…Our results thus differ from the ones reported by Alwis and Haberman (2020) who found that people are biased toward the mean when reporting the pleasure of one image among four. This difference is most likely due to differences between our and their experimental paradigm.…”
Section: Without Precuing People Cannot Faithfully Report One Of Foucontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results thus differ from the ones reported by Alwis and Haberman (2020) who found that people are biased toward the mean when reporting the pleasure of one image among four. This difference is most likely due to differences between our and their experimental paradigm.…”
Section: Without Precuing People Cannot Faithfully Report One Of Foucontrasting
confidence: 99%
“…The pleasure of images that were otherwise highly pleasurable (pleasure >4.6, on average across participants) was diminished. This effect does not represent a bias towards the mean-the effect that has been observed when people report other properties of one target among several distractors (e.g., Alwis & Haberman, 2020;Brady & Alvarez, 2011; Whitney, 2009;Maule et al, 2014;Zhang & Luck, 2008). Importantly, we did consider the average-biased model, but found that its performance is consistently worse than the one of either a faithful or a high-pleasure attenuation model (see Fig.…”
Section: Without Precuing People Cannot Faithfully Report One Of Foumentioning
confidence: 77%
See 1 more Smart Citation
“…Additionally, prior work found that observers cannot faithfully report the single pleasure of a visual stimulus in an array of four stimuli when presented very briefly (200 ms), but that they instead report overall diminished pleasure (Brielmann & Pelli, 2021). This result stands in contrast to similar work that presented multiple images for a longer duration (1.5 s) and found that observers are biased toward the mean pleasure of the entire array (Alwis & Haberman, 2020). When presented with multiple images for a longer period, observers likely had time to attend to each stimulus in a serial manner, which then subsequently resulted in averaging across all stimuli when making a judgment.…”
Section: Judgments Of Simultaneously Presented Imagescontrasting
confidence: 99%
“…The authors found that participants could not faithfully report the pleasure of a single image unless cued to which image they would be rating ahead of time, and that observers also did not faithfully report the average pleasure of four images (Brielmann & Pelli, 2021). With longer presentation durations of 1.5 s (vs. 200 ms in Brielmann & Pelli, 2020) and a homogeneous image set, pleasure ratings of one scene among three others were found to be biased toward the mean pleasure of the presented scenes (Alwis & Haberman, 2020).…”
mentioning
confidence: 99%